SURGICAL MANAGEMENT OF SALIVARY FISTULA IN CATTLE - Tyagi, SP; Kumar, Amit (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Trauma and occlusion of stenson’s duct occur infrequently in cattle, buffalo and camels (Tyagi and Singh. 2006). The occlusion of the oral opening of the duct by the feed particle may cause its distension due to impediment in the flow of the saliva ultimately causing rupture of the duct.There were also reported cases of obstructive sialolithiasis in animals which give rise to salivary cysts (Joshi et al. 2003, Ali et al. 1978 and Barvalia et al. 1992). The leakage of the saliva into the surrounding tissue along with local tissue reaction may lead to development of the swelling in the region. The condition often referred to as salivary cyst. Salivary cysts are mainly acquired in origin but rarely, it can be congenital. Standard treatment of salivary cyst like destruction of parotid gland or radical excision of the parotid gland has limitation of re-occurrence and risky surgery respectively. More over both methods possess the risk of xerostomia. So another alternative was tried in present study for management of salivary cysts to overcome above mentioned limitations.